Evaluation Of Character Education Programs In Islamic Boarding Schools: Using The Cipp Evaluation Model To Measure Long-Term Impact - Masdiya; Ahmad Sopian; Muhammad Izzudin; Aqila Amalia; Muhammad Yasir; Rohman Latif; Reni Fitriyanti (CV. Doki Course and Training, 2025)
This integrative literature review examines the evaluation of character education programmes in Indonesian pesantren through the CIPP (Context, Input, Process, Product) model, with particular attention to long-term impact on alumni character development. A structured search on Google Scholar yielded 42 peer-reviewed sources published between 2020 and 2025, which were synthesised thematically across the four CIPP domains. Findings indicate that while institutional vision aligns strongly with national character education policy, critical gaps persist in pedagogical training, budgetary allocation, and implementation fidelity of less structured activities. Product evaluation reveals that dispositional traits such as integrity and social responsibility demonstrate greater long-term durability than ritual-bound behaviours, with alumni community engagement serving as a significant moderating factor. The review advocates for a culturally contextualised adaptation of the CIPP model that incorporates pesantren-specific elements, including the spiritual authority of the kyai and the hidden curriculum. Practical recommendations include institutionalised alumni tracking, increased character-specific funding, and periodic CIPP-based programme assessments.